Pengaruh Metode Talking Stick Terhadap Pembelajaran IPA Kelas IV Sekolah Dasar - Recika Ranna Harayo; Adam Ilham Said; Nur Ngazizah (Indonesian Journal of Elementary and Childhood Education, 2022)
Based on the results obtained from observations and interviews that have been carried out, it turns out that there are several things that have not met the criteria and some have met the criteria, things that have not met the criteria are in learning facilities that are not equipped such as no LCD and projector, so that learning is hampered if the teacher wants to display learning images or videos. Then the thing that has met the criteria is when we made direct observations to SD Negeri Kledung Kradenan Purworejo. The completeness of learning in the classroom has been facilitated, such as the Syllabus, rpp, as well as for the cleanliness and tidiness of the school environment is good, so that the teaching and learning process can run systematically and as expected. So it can be concluded that the application of the Talking Stick learning model in grade 4 of SD Negeri Kledung Kradenan Purworejo, Central Java can improve student learning outcomes in natural science subjects. It has been proven through the results of interviews and observations at SD Negeri Kledung Kradenan Purworejo, Central Java, it turns out that students are more enthusiastic in learning when using the Talking Stick learning model than without using the Talking Stick learning model. That way in this study it is suggested that teachers can use the Talking Stick learning model. Because using the Talking Stick model can increase interest in learning and provide motivation to students in learning Natural Sciences.